PARITY AND EMPLOYMENT STATUS TOWARDS BREAST MILK EXPENDITURE ON BREASTFEEDING MOTHER 0-6 MONTHS - Ratna Sari Hardiani (NurseLine Journal, 2017)
The achievement of exclusive breastfeeding is still not reach the maximum target, although the achievement target in Jember is 80%. Arjasa is one of districts with the lowest breastfeeding coverage, its amount to 14.40%. Discontinuity of breastfeeding expenditure became one of the causes. This research explained the correlation of parity and employment with breast milk expenditure on breastfeeding mother 0-6 months. This research was a correlation study with cross sectional approach which consisted of 30 breastfeeding mothers in Public Health Center of Arjasa, Jember. Data were analyzed by Spearman Rho test (α<0.05). The results showed that most of mothers were primiparous and had employment as farm labor, and the majority of breast milk expenditure was not smooth. Mother’s employment status had a correlation with breastfeed expenditure (p=0.017), whereas parity did not have correlation to breastfeed expenditure (p=0.517). Based on the results, mother’s employment can affect the breast milk expenditure. Health workers should improve health education and motivation about breast milk management on breastfeeding mothers involving their family support.